Avian influenza overview March – April 2023 - European Food Safety Authority, European Centre for Disease Prevention and Control, European Union Reference Laboratory for Avian Influenza; Cornelia Adlhoch; Alice Fusaro; José L Gonzales; Thijs Kuiken; Grazina Mirinaviciute; Éric Niqueux; Karl Stahl; Christoph Staubach; Calogero Terregino; Alessandro Broglia; Lisa Kohnle; et al. (EFSA Journal)
Abstract Between 2 March and 28 April 2023, highly pathogenic avian influenza (HPAI) A(H5Nx) virus, clade 2.3.4.4b, outbreaks were reported in domestic (106) and wild (610) birds across 24 countries in Europe. Poultry outbreaks occurred less frequently compared to the previous reporting period and compared to spring 2022. Most of these outbreaks were classified as primary outbreaks without secondary spread and some of them associated with atypical disease presentation, in particular low mortality. In wild birds, black‐headed gulls continued to be heavily affected, while also other threatened wild bird species, such as the peregrine falcon, showed increased mortality. The ongoing epidemic in black‐headed gulls, many of which breed inland, may increase the risk for poultry, especially in July–August, when first‐year birds disperse from the breeding colonies. HPAI A(H5N1) virus also continued to expand in the Americas, including in mammalian species, and is expected to reach the Antarctic in the near future. HPAI virus infections were detected in six mammal species, particularly in marine mammals and mustelids, for the first time, while the viruses currently circulating in Europe retain a preferential binding for avian‐like receptors. Since 13 March 2022 and as of 10 May 2023, two A(H5N1) clade 2.3.4.4b virus detections in humans were reported from China (1), and Chile (1), as well as three A(H9N2) and one A(H3N8) human infections in China. The risk of infection with currently circulating avian H5 influenza viruses of clade 2.3.4.4b in Europe remains low for the general population in the EU/EEA, and low to moderate for occupationally or otherwise exposed people.